2015
DOI: 10.4148/1936-0487.1070
|View full text |Cite
|
Sign up to set email alerts
|

Review Strategies to Recruit and Retain Rural Patient Participating Self-management Behavioral Trials

Abstract: Self-management plays a vital role in improving health outcomes and reducing costs in patients with cardiovascular disease (CVD) and associated risk factors. Based on existing studies, rural residents with CVD and/or risk factors show low engagement in self-management behaviors. Due to low participation in behavioral intervention trials, the most promising mechanism to promote self-management among rural populations is unknown. In turn, the purpose of this article is to review the evidence that supports strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…However, our study did have more female participants than have been reported in other studies. During recruitment, we found women more willing than men to participate in the study [ 15 , 25 , 26 ]. Field notes indicated women were more likely to believe SM had positive effects on their sustained independence and HF symptom relief, felt more isolated and more often sought social interactions with the research team, and had greater interest in learning SM strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study did have more female participants than have been reported in other studies. During recruitment, we found women more willing than men to participate in the study [ 15 , 25 , 26 ]. Field notes indicated women were more likely to believe SM had positive effects on their sustained independence and HF symptom relief, felt more isolated and more often sought social interactions with the research team, and had greater interest in learning SM strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This may help ensure that the study sample reflects the national sociodemographic and clinical characteristics. Vulnerable individuals from minorities and rural areas may be engaged in HPR through community-based formal and informal organizations and stakeholders, such as places of worship, religion study groups, community centers, and through community leaders, chiefs, and elders [ 20 ]. This strategy has rarely been used in population-based or clinical HPR but has been widely used in community-based participatory research.…”
Section: Challenges and Potential Solutionsmentioning
confidence: 99%
“…Similarly, 94% of young adults aged 18 to 29 years and 65% of adults in rural communities own a smartphone [20]. Adoption of web-based surveys for data collection is likely to appeal to young people, who grew up with computers and use them in virtually all aspects of their lives, while reducing transportation and other costs that serve as barriers to engaging in traditional clinical trials [21][22][23][24]. With respect to retaining young people in longitudinal studies, there was no clear recommendation on incentives to maximize retention, as previous studies had identified multiple means, including increasing participant payments, conducting sweepstakes, providing bonuses, and sending reminder postcards [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%